Discrimination and learning of temporal input sequences in a cerebellar Purkinje cell model - Tamura, Kaaya; Yamamoto, Yuki; Kobayashi, Taira; Kuriyama, Rin; Yamazaki, Tadashi (Frontiers in Cellular Neuroscience, 2023)
Temporal information processing is essential for sequential contraction of various muscles with the appropriate timing and amplitude for fast and smooth motor control. These functions depend on dynamics of neural circuits, which consist of simple neurons that accumulate incoming spikes and emit other spikes. However, recent studies indicate that individual neurons can perform complex information processing through the nonlinear dynamics of dendrites with complex shapes and ion channels. Although we have extensive evidence that cerebellar circuits play a vital role in motor control, studies investigating the computational ability of single Purkinje cells are few. We found, through computer simulations, that a Purkinje cell can discriminate a series of pulses in two directions (from dendrite tip to soma, and from soma to dendrite),as cortical pyramidal cells do. \color{red}Such direction sensitivity was observed in whatever compartment types of dendrites (spiny, smooth, and main), although they have different sets of ion channels. We found that the shortest and longest discriminable sequences lasted for 60 ms (6 pulses with 10 ms interval) and 4,000 ms (20 pulses with 200 ms interval), respectively. and that the ratio of discriminable sequences within the region of the interesting parameter space was, on average, 3.3 % (spiny), 3.2 % (smooth), and 1.0 % (main). \color{black}For the direction sensitivity, a T-type $\text{Ca}^{2+}$ channel was necessary, in contrast with cortical pyramidal cells that have $N$-methyl-$D$-aspartate receptors (NMDARs). Furthermore, we tested whether the stimulus direction can be reversed by learning, specifically by simulated long-term depression, and obtained positive results. Our results show that individual Purkinje cells can perform more complex information processing than is conventionally assumed for a single neuron, and suggest that Purkinje cells act as sequence discriminators, a useful role in motor control and learning.